Which competitive advantages can firms really obtain from ISO14001 certification? - Josefina Lucia Murillo-Luna; Juan Carlos Ramón-Solans-Prat (Journal of Industrial Engineering and Management (JIEM), 2008)
Ten years after the introduction of ISO14001, in this paper we present empirical evidence about the competitive advantages that managers associate to this environmental practice, from a sample of industrial firms located in Spain. The results indicate that the potential competitive advantages are: improvement of the internal efficiency, differentiation advantages, attention to the stakeholders' requirements, enhancement of the competitive position in the sector and financial savings. Nevertheless managers' expectations of improving internal efficiency might be the real reason that encourages firms to make the voluntary decision of investing in ISO14001 certification.
Keywords: 650; ISO14001; competitive advantages; industrial firms